Low-dose mRNA-1273 COVID-19 vaccine generates durable memory enhanced by cross-reactive T cells - Mateus, Jose; Dan, Jennifer M.; Zhang, Zeli; Rydyznski Moderbacher, Carolyn; Lammers, Marshall; Goodwin, Benjamin; Sette, Alessandro; Crotty, Shane; Weiskopf, Daniela (Science (American Association for the Advancement of Science), 2021)
Low-dose messenger RNA (mRNA) vaccines potentially allow health providers to administer more doses from a limited vaccine supply and can be less reactogenic. Whether low-dose COVID-19 mRNA vaccines generate immune responses comparable to currently approved doses remains an open question, however. Mateus et al . report the results of a clinical trial comparing patients who received a 25-μg mRNA-1273 (Moderna) COVID-19 vaccine to 100-μg mRNA-1273 COVID-19 vaccinees and severe acute respiratory syndrome coronavirus 2–infected individuals. The low-dose Moderna vaccine generated long-lived T cell immunity that was equivalent between younger and older patients and that could be enhanced by the presence of cross-reactive T cells. Moreover, antibody and T cell responses induced by the low-dose vaccine were comparable to natural infection and about half as strong as those seen with high-dose vaccination. —STS A reduced dose of the Moderna SARS-CoV-2 vaccine induces long-lived T cell and antibody responses comparable to natural infection. Vaccine-specific CD4 + T cell, CD8 + T cell, binding antibody, and neutralizing antibody responses to the 25-μg Moderna messenger RNA (mRNA)–1273 vaccine were examined over the course of 7 months after immunization, including in multiple age groups, with a particular interest in assessing whether preexisting cross-reactive T cell memory affects vaccine-generated immunity. Vaccine-generated spike-specific memory CD4 + T cells 6 months after the second dose of the vaccine were comparable in quantity and quality to COVID-19 cases, including the presence of T follicular helper cells and interferon-γ–expressing cells. Spike-specific CD8 + T cells were generated in 88% of subjects, with equivalent memory at 6 months post-boost compared with COVID-19 cases. Lastly, subjects with preexisting cross-reactive CD4 + T cell memory exhibited stronger CD4 + T cell and antibody responses to the vaccine, demonstrating the biological relevance of severe acute respiratory syndrome coronavirus 2–cross-reactive CD4 + T cells.